Master your time, master your life : the breakthrough system to get more results, faster, in every area of your life - Tracy, Brian (TarcherPerigee, 2016)
"This life-changing book from the bestselling author of Eat That Frog! provides a unique program for determining WHAT to do WHEN, and managing all of the many details of our lives. We may feel stuck and unable to take certain items off our "To Do" lists for one simple reason: the timing isn't right. In Master Your Time, Master Your Life, international speaker, productivity expert, and bestselling author Brian Tracy explains why tackling the right project at the right time is of the utmost importance. By using our time in the appropriate way in the most important areas of our lives we will accomplish much more, faster and more easily than we ever thought possible! Based on the most recent research in the field of productivity, as well as the author's personal experiences and those of his clients, Tracy's method involves identifying the ten different "times" in which we operate, and the unique approach required for each of these in order to perform at our very best. Master Your Time, Master Your Life provides simple steps we can use to figure out when we will be most productive for a specific task and when we should move on to the next item on our list, outlining a framework for optimal productivity that will change lives forever!"--